Fish Oil Protects Wild Type and Uncoupling Protein 1‐Deficient Mice from Obesity and Glucose Intolerance by Increasing Energy Expenditure. Issue 7 (17th January 2019) - Oliveira, Tiago E.; Castro, Érique; Belchior, Thiago; Andrade, Maynara L.; Chaves‐Filho, Adriano B.; Peixoto, Albert S.; Moreno, Mayara F.; Ortiz‐Silva, Milene; Moreira, Rafael J.; Inague, Alex; Yoshinaga, Marcos Y.; Miyamoto, Sayuri; et al.
Abstract : Scope: The mechanisms and involvement of uncoupling protein 1 (UCP1) in the protection from obesity and insulin resistance induced by intake of a high‐fat diet rich in omega‐3 (n‐3) fatty acids are investigated. Methods and results: C57BL/6J mice are fed either a low‐fat (control group) or one of two isocaloric high‐fat diets containing either lard (HFD) or fish oil (HFN3) as fat source and evaluated for body weight, adiposity, energy expenditure, glucose homeostasis, and inguinal white and interscapular brown adipose tissue (iWAT and iBAT, respectively) gene expression, lipidome, and mitochondrial bioenergetics. HFN3 intake protected from obesity, glucose and insulin intolerances, and hyperinsulinemia. This is associated with increased energy expenditure, iWAT UCP1 expression, and incorporation of n‐3 eicosapentaenoic and docosahexaenoic fatty acids in iWAT and iBAT triacylglycerol. Importantly, HFN3 is equally effective in reducing body weight gain, adiposity, and glucose intolerance and increasing energy expenditure in wild‐type and UCP1‐deficient mice without recruiting other thermogenic processes in iWAT and iBAT, such as mitochondrial uncoupling and SERCA‐mediated calcium and creatine‐driven substrate cyclings. Conclusion: Intake of a high‐fat diet rich in omega‐3 fatty acids protects both wild‐type and UCP1‐deficient mice from obesity and insulin resistance by increasing energy expenditure through unknown mechanisms. Abstract : Intake of a high‐fat diet (HFD) rich in fish oil is equally effective in reducing body weight gain, adiposity, and glucose intolerance and increasing energy expenditure in wild‐type and UCP1 knockout mice. These findings support the notion that UCP1‐mediated nonshivering thermogenesis may not be involved in the increase in energy expenditure and protection from diet‐induced obesity and glucose intolerance induced by the intake of an HFD rich in omega‐3 fatty acids.